Clinical, morphological and genetic characteristics of young patients with hypertrophic cardiomyopathy with indications for implantable cardioverter-defibrillator - V. G. Davydova; A. Ya. Gudkova; A. N. Krutikov; A. A. Poliakova; A. A. Kostareva (Российский кардиологический журнал)
Aim. To study the clinical, morphological and genetic characteristics of young patients with hypertrophic cardiomyopathy (HCM) with indications for primary and secondary prevention of sudden cardiac death (SCD).Material and methods. The study included 44 young patients with HCM who were examined in accordance with national clinical guidelines for HCM (2020). The AHA HCM SCD Calculator was used to calculate the risk of SCD. The genetic study was performed using a target panel of 108 genes associated with cardiomyopathies.Results. In the study cohort, young patients in 72,7% of cases (n=32) had from 1 to 3 cardiometabolic risk factors (on average 1,53±0,8).The age of 18 patients with indications for implantable cardioverter-defibrillator (ICD) ranged from 18 to 44 years (28,8±2,2). The age at diagnosis was 18,5±7,4 years, while the asymptomatic period lasted 6,4±0,9 years. The estimated risk of SCD ranged from 3,11 to 20,71% (6,15 [4,67; 7,32]). In 83,3% of cases (n=15), familial HCM was diagnosed, while 50% (n=9) had a positive family history of SCD. In the subgroup of patients with indications for ICD, genetic variants with pathogenic significance (class IV and V) encoding the production of sarcomere proteins were detected in 6 of 9 probands (66,7%).In patients with indications for ICD (n=18), compared to patients without it (n=26), the diagnosis of HCM was more often established in childhood and adolescence (61,1% vs 23%, p=0,01). In patients with indications for ICD, the reverse curvature hypertrophy of the interventricular septum was significantly more often diagnosed (72,2% vs 38,5%, p=0,028). Among patients with indications for ICD, the proportion of people with low physical activity was 50% (n=9), of which 55,6% (n=5) were diagnosed with overweight/class 1 obesity.Conclusion. Childhood and adolescence at the time of diagnosis of HCM and reverse curvature hypertrophy of the interventricular septum are significantly more common in young patients with indications for ICD.